Chronic Migraine Pathophysiology and Treatment: A Review of Current Perspectives - Mungoven, Tiffani J.; Henderson, Luke A.; Meylakh, Noemi (Frontiers in Pain Research, 2021)
Chronic migraine is a disabling neurological disorder that imposes a considerable burden on individual and socioeconomic outcomes. Chronic migraine is defined as headaches occurring on at least 15 days per month with at least eight of these fulfilling the criteria for migraine. Chronic migraine typically evolves from episodic migraine as a result of increasing attack frequency and/or several other risk factors that have been implicated with migraine chronification. Despite this evolution, chronic migraine likely develops into its own distinct clinical entity, with unique features and pathophysiology separating it from episodic migraine. Furthermore, chronic migraine is characterized with higher disability and incidence of comorbidities in comparison to episodic migraine. While existing migraine studies primarily focus on episodic migraine, less is known about chronic migraine pathophysiology. Mounting evidence on aberrant alterations suggest that pronounced functional and structural brain changes, central sensitization and neuroinflammation may underlie chronic migraine mechanisms. Current treatment options for chronic migraine include risk factor modification, acute and prophylactic therapies, evidence-based treatments such as onabotulinumtoxinA, topiramate and newly approved calcitonin gene-related peptide or receptor targeted monoclonal antibodies. Unfortunately, treatments are still predominantly ineffective in aborting migraine attacks and decreasing intensity and frequency, and poor adherence and compliance with preventative medications remains a significant challenge. Novel emerging chronic migraine treatments such as neuromodulation offer promising therapeutic approaches that warrant further investigation. The aim of this narrative review is to provide an update of current knowledge and perspectives regarding chronic migraine background, pathophysiology, current and emerging treatment options with the intention of facilitating future research into this debilitating and largely indeterminant disorder.